1999
DOI: 10.1212/wnl.53.8.1665
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of cognitive impairment in ALS

Abstract: Bulbar-onset ALS patients with cognitive impairments and neuronal loss in the anterior cingulate gyrus subsequently developed more profound neuropsychological dysfunction whereas both language and speech capabilities remained relatively preserved. Of note, the absence of bulbar signs did not predict an absence of cognitive decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
139
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(152 citation statements)
references
References 22 publications
11
139
2
Order By: Relevance
“…Previously, some studies have found that people with bulbar onset of ALS are more likely to have cognitive impairment than those with spinal onset [39,53,54], but others do not [33,35,55]. In our study, the site of onset had no effect of the presence of cognitive impairment as determined by the ACE-III, but site of onset influenced cognitive impairment based on FAB logistic regression results.…”
Section: Accepted Manuscriptcontrasting
confidence: 58%
See 3 more Smart Citations
“…Previously, some studies have found that people with bulbar onset of ALS are more likely to have cognitive impairment than those with spinal onset [39,53,54], but others do not [33,35,55]. In our study, the site of onset had no effect of the presence of cognitive impairment as determined by the ACE-III, but site of onset influenced cognitive impairment based on FAB logistic regression results.…”
Section: Accepted Manuscriptcontrasting
confidence: 58%
“…Some studies have found cognitive impairment to be more common in people with bulbar onset than limb onset of ALS [32]. However, other studies suggest that site of onset has no influence on the presence of cognitive impairment [33][34][35]. Therefore further information is required.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…31 We are aware of a single MRSI study of the anterior cingulate in ALS; it showed reduced NAA/Cr specifically in those with bulbar onset disease. 32 Convincing evidence for thalamic involvement in ALS has not been forthcoming from routine postmortem or standard anatomic imaging studies. There have been very few postmortem studies that have specifically examined the thalamus.…”
Section: Discussionmentioning
confidence: 99%